2005
DOI: 10.1242/jcs.02297
|View full text |Cite
|
Sign up to set email alerts
|

Secretory pathway Ca2+-ATPase (SPCA1) Ca2+ pumps, not SERCAs, regulate complex [Ca2+]i signals in human spermatozoa

Abstract: The sarcoplasmic-endoplasmic reticulum Ca2+-ATPase (SERCA) inhibitors thapsigargin (0.1-1 μM) and cyclopiazonic acid (10 μM), failed to affect resting [Ca2+] in human spermatozoa. Slow progesterone-induced [Ca2+ i]i oscillations in human spermatozoa, which involve cyclic emptying-refilling of an intracellular Ca2+ store were also insensitive to these inhibitors. Non-selective doses of thapsigargin (5-30 μM, 50-300 times the saturating dose for SERCA inhibition), caused elevation of resting [Ca2+]i and partial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 48 publications
4
60
1
Order By: Relevance
“…intracellular Ca 2þ pump in these cells because both functional and immunocytochemical tests failed to show the presence of SERCAs (Harper et al 2005). A similar picture arises from sea-urchin sperm cells, which lack SERCAs.…”
Section: Spca1mentioning
confidence: 90%
“…intracellular Ca 2þ pump in these cells because both functional and immunocytochemical tests failed to show the presence of SERCAs (Harper et al 2005). A similar picture arises from sea-urchin sperm cells, which lack SERCAs.…”
Section: Spca1mentioning
confidence: 90%
“…Western blotting detected secretory pathway Ca 2ϩ -ATPase (SPCA1) in human spermatozoa, but not SERCA, and immunostaining showed that SPCA1 is localized in the head-tail junction, where the Ca 2ϩ oscillations are observed (238). A fluorescently labeled ryanodine binds to the same sites (238). These results strongly suggest that SPCA1 is involved in refilling Ca 2ϩ during the Ca 2ϩ oscillations.…”
Section: Channels (329)mentioning
confidence: 93%
“…Low concentrations (50 -100 M) of ryanodine accelerated the oscillations, while high doses (500 M) reduced them. TMB-8 and tetracaine, inhibitors of Ca 2ϩ release from Ca 2ϩ stores, arrested the oscillations, suggesting the importance of store emptying/refilling cycles in this process (238). The progesterone-induced oscillations are relatively insensitive to thapsigargin or cyclopiazonic acid, inhibitors of SERCA, but sensitive to bis-phenol, a nonspecific Ca 2ϩ -ATPase inhibitor.…”
Section: Channels (329)mentioning
confidence: 95%
See 1 more Smart Citation
“…Since vanadate inhibits the dynein-ATPase and also the sperm fl agellar motility (Gibbons et al, 1978;Kobayashi et al, 1978), the vanadate-sensitive Mg 2+ -ATPase activity of the axoneme-containing fractions shown in our results might represent the dynein-ATPase activity of the human sperm. The remaining vanadate-insensitive Mg 2+ -ATPase activity of the preparations is probably the result of the activity of different ATPases and phosphatases present in the human sperm (Harper et al, 2005;Tomes et al, 2004).…”
Section: +mentioning
confidence: 98%